ISLAMIC CONSUMPTION ETHICS ON SKINCARE - Noor Iffatin Nadhifah (STAI AL-HIDAYAT Lasem, 2024)
The large number of skincare products circulating in society is a special concern for consumers to be careful about the ingredients of skincare and its suitability for the consumer's skin type. This study aims to provide consumer insight into consuming skincare according to Islamic consumption ethics. The research method used is the descriptive method used to collect actual data, this method generally uses a qualitative approach, so that a researcher when going into the field does not bring a data collection tool, but directly conducts observations or observations of evidence while collecting data and conducting analysis.